High-hardness Ta-Hf-W nitride film and preparation method thereof

Ta-Hf-W nitride films were prepared through reactive multi-target DC magnetron sputtering technology, which solved the problem of insufficient research on nitride coatings in refractory metal systems such as Ta, Hf, W, and achieved high hardness and wear resistance nitride films are suitable for material modification under extreme service conditions.

CN119194352AActive Publication Date: 2024-12-27NAT INNOVATION INST OF DEFENSE TECH PLA ACAD OF MILITARY SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411327677.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

In the prior art, there are few researches on ternary and quadruple system nitride coatings of refractory metals such as Ta, Hf, W, etc., and lacks nitride films with high hardness and wear resistance, making it difficult to meet the material needs under extreme service conditions. .

Method used

Ta-Hf-W nitride films are prepared by reactive multi-target DC magnetron sputtering technology. By adjusting the sputtering power, gas flow and angle of the target material, a single-phase face-centered cubic crystal structure with small surface roughness is prepared. , TaaHfbWcNd nitride film with high hardness and elastic modulus.

Benefits of technology

The Ta-Hf-W nitride film with high hardness and wear resistance is suitable for aerospace, national defense and other fields, improves the surface strength and wear resistance of the material, and has a wide range of industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194352A_ABST
    Figure CN119194352A_ABST
Patent Text Reader

Abstract

The invention discloses a high-hardness Ta-Hf-W nitride film and a preparation method and application thereof, the nitride film is composed of Ta, Hf, W and N atoms, and the chemical formula is TaaHfbWcNd, wherein a, b, c and d all represent atomic ratios, and the value range of a is 17-21; the value range of b is 7 to 17; the value range of c is 29 to 31; the value range of d is 31-47, and a + b + c + d is equal to 100; the Ta-Hf-W nitride film is prepared by adopting a reactive multi-target direct-current magnetron sputtering technology, has a single-phase face-centered cubic crystal structure, the surface roughness of the film is 1.85-2.20 nm, the hardness is 28.4-36.1 GPa, the elastic modulus is 308.3-357.2 GPa, and the Ta-Hf-W nitride film is applied to surface modification of structural materials in the field of extreme service conditions, so that the strength, the hardness and the wear resistance of the surfaces of the materials are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a high-hardness Ta-Hf-W nitride film and a preparation method thereof. Background Art

[0002] In recent years, high entropy ceramics, especially high entropy nitride (HENs) ceramic materials, have attracted extensive attention due to their excellent properties. It is reported that the introduction of nitrogen into high entropy alloy solid solution has a significant effect on the structure and microstructure properties, and can improve the mechanical properties to a certain extent.

[0003] Although the research on high entropy alloys is mainly focused on bulk materials, its strengthening theory has been extended to ceramic thin film materials based on the concept of high entropy alloys. The preparation of high entropy boride, carbide, nitride and oxide films can be achieved by adding non-metallic elements (such as B, C, N, or O). In particular, high entropy nitride films have higher hardness, wear resistance and oxidation resistance than high entropy alloys, so they have extremely high potential application value as hard protective films.

[0004] Traditional nitride coatings, such as TiN and CrN, are used as wear-resistant coatings in many industrial fields such as cutting and forming tools, mechanical parts, etc. due to their high hardness. In order to improve the performance of specific tools and molds in applications, new hard coatings need to be continuously developed. Ternary and quaternary nitride coatings, such as TiAlN, TiCN and TiSiCN, have been developed by incorporating metal and metalloid elements.

[0005] Magnetron sputtering has the characteristics of high deposition rate, good film quality, controllable performance, good bonding strength with the substrate and few impurities, making it one of the most common methods for preparing thin films. Magnetron sputtering deposition most often adopts the form of single-target sputtering, that is, the sputtering target is a single alloy target. This technology can achieve precise control of the stoichiometric ratio of the film components; but its disadvantage is that the preparation of alloy targets is complicated and the cost is high. With the continuous improvement of the preparation technology level, multi-target magnetron sputtering process has been increasingly applied to the preparation research of multi-principal thin films. Multi-target magnetron sputtering uses multiple pure metal targets or binary alloy targets, which can effectively avoid the complex preparation process of a single alloy target; and by changing the sputtering power of the target, the sputtering time of the target and the angle of the target perpendicular to the center line of the sample stage, a film with diversified components can be prepared, making the film preparation more flexible and conducive to high-throughput screening of film composition and performance.

[0006] However, there has not been much research on refractory metals such as Ta, Hf, and W. Therefore, this patent uses refractory metals such as Ta, Hf, and W as the main elements to deposit nitride films through a reactive multi-target magnetron sputtering process. Summary of the invention

[0007] In view of the problem that a large amount of research has not been conducted on nitride coatings of ternary and quaternary systems for refractory metals such as Ta, Hf, and W in the prior art, the present invention provides a high-hardness Ta-Hf-W nitride film and a preparation method thereof. The Ta-Hf-W nitride film is prepared by reactive multi-target DC magnetron sputtering technology. The nitride film has a quaternary component number, a single-phase face-centered cubic crystal structure, a small surface roughness, and high hardness and elastic modulus properties.

[0008] The present invention provides a Ta a Hf b W c N d Nitride film, which is made by reactive multi-target DC magnetron sputtering technology, has a surface roughness of 1.85-2.20 nm, a hardness of 28.4-36.1 GPa, and an elastic modulus of 308.3-357.2 GPa. It has a broader application prospect and can be used for surface modification of structural materials in extreme service conditions such as aerospace, national defense, chemical industry, etc., to improve the strength, hardness and wear resistance of the material surface.

[0009] The present invention provides a high-hardness Ta-Hf-W nitride film and a preparation method thereof. The nitride film is composed of Ta, Hf, W and N atoms, and the preparation method comprises the following steps:

[0010] (1) The substrate was ultrasonically cleaned in anhydrous ethanol, rinsed with deionized water, and the surface was blown dry with dry compressed nitrogen, and then fixed on the sample stage;

[0011] (2) placing the required high-purity metal targets Ta, Hf and W on three DC sputtering target positions in the deposition chamber, and adjusting the angle of the metal target perpendicular to the center line of the sample stage and the vertical distance between the metal target and the substrate respectively;

[0012] (3) First, the vacuum degree of the deposition chamber is evacuated to the required experimental conditions, and then high-purity argon and nitrogen are introduced, and the required gas flow rates are set respectively, the working gas pressure of the deposition chamber is adjusted, the sputtering power of each metal target is set, and the substrate is covered with a baffle and the target is pre-sputtered;

[0013] (4) Then, the rotation speed of the substrate is set and the baffle is opened to perform formal sputtering coating, and a Ta-Hf-W nitride film is obtained according to the required process parameters.

[0014] The invention adopts a reactive multi-target DC magnetron sputtering film deposition method to obtain a Ta-Hf-W nitride film with uniform composition, small surface roughness, high hardness and elastic modulus.

[0015] The purpose of the present invention is achieved through the following technical solutions:

[0016] A high hardness Ta-Hf-W nitride film, specifically Ta a Hf b W c N d The nitride film is composed of Ta, Hf, W, and N atoms, and the chemical formula is: Ta a Hf b W c N d ; wherein a, b, c and d all represent atomic ratios, the value range of a is: 17-21; the value range of b is: 7-17; the value range of c is: 29-31; the value range of d is: 31-47, and a+b+c+d=100; Ta, Hf, and W targets are prepared by reactive magnetron sputtering thin film deposition at set sputtering powers and different nitrogen gas flow rates to obtain Ta a Hf b W c N d Nitride film; the nitride film has four components, a single-phase face-centered cubic (FCC) crystal structure, a surface roughness of 1.85 to 2.20 nm, a hardness of 28.4 to 36.1 GPa, and an elastic modulus of 308.3 to 357.2 GPa.

[0017] The above-mentioned method for preparing a high-hardness Ta-Hf-W nitride film comprises the following steps:

[0018] 1) Place the substrate in anhydrous ethanol and perform ultrasonic cleaning for 10 minutes to remove pollutants attached to the surface of the substrate, and then rinse the substrate with deionized water;

[0019] 2) Blow dry the cleaned substrate with compressed nitrogen to make the surface of the substrate clean and prevent water stains from remaining;

[0020] 3) Fix the substrate with its smooth surface facing downward on a furnace plate, fix the furnace plate on a sample stage in a deposition chamber of a magnetron sputtering thin film deposition device, and rotate the sample stage baffle to adjust it to a position that completely covers the substrate;

[0021] 4) placing Ta, Hf and W metal bulk targets respectively on three different DC target positions in the deposition chamber, and adjusting the angle of each target perpendicular to the center line of the sample stage and the vertical distance between each target and the sample stage;

[0022] The targets of Ta, Hf and W are all high-purity metal blocks with a purity of ≥99.95%, a diameter of 60 mm and a thickness of 3 to 5 mm;

[0023] The angle of the target relative to the center line of the sample stage is 20 to 40 degrees; the vertical distance between the metal target of Ta, Hf, W and the sample stage is 5 to 15 cm;

[0024] 5) First, use a mechanical pump to evacuate the deposition chamber to a vacuum level of less than 8.0 Pa, and then use a molecular pump to evacuate the deposition chamber to a vacuum level of less than 6.0×10 -4 ~8.0×10 -4 Pa;

[0025] 6) Then, argon and nitrogen are introduced into the deposition chamber, and the gas flow rates are adjusted respectively, and the working pressure is adjusted to 0.7-0.9 Pa, and the DC power supply of the corresponding target is turned on, and the sputtering power of the target is set respectively, and the target is pre-sputtered for 10-15 minutes to remove impurities such as oxides formed on the surface of the target, wherein the sputtering power of the Ta target is 100 W, the sputtering power of the Hf target is 100 W, and the sputtering power of the W target is 100 W;

[0026] 7) Setting the rotation rate of the sample stage to 15-30 r / min, opening the substrate baffle, and performing sputtering deposition on the smooth surface of the substrate for 1 h to obtain a thin film;

[0027] 8) After the sputtering deposition is completed, turn off the DC power supply, turn off the argon and nitrogen, stop the rotation of the sample stage, and let the film cool to room temperature under vacuum before taking it out to reduce oxidation contamination. Finally, Ta is obtained on the substrate. a Hf b W c N d The nitride film is a high-hardness Ta-Hf-W nitride film. The nitride film is composed of Ta, Hf, W, and N atoms, and the chemical formula is: Ta a Hf b W c N d ; Wherein, a, b, c and d all represent atomic ratios, the value range of a is: 17~21; the value range of b is: 7~17; the value range of c is: 29~31; the value range of d is: 31~47, and a+b+c+d=100; the number of components of the nitride film is quaternary, with a single-phase face-centered cubic (FCC) crystal structure, a surface roughness of 1.85~2.20nm, a hardness of the film is 28.4~36.1GPa, and an elastic modulus is 308.3~357.2GPa.

[0028] Furthermore, before the ultrasonic cleaning in step 1), the smooth surface of the substrate is polished with a damping cloth.

[0029] Furthermore, the substrate in step 1) is a single crystal silicon wafer, and the single crystal silicon wafer is a commercial P-type wafer with a crystal orientation of <100> .

[0030] Furthermore, in the ultrasonic cleaning described in step 1), the ultrasonic frequency is 60 to 80 Hz.

[0031] Furthermore, the angle of the target material described in step 4) relative to the center line of the sample stage is 20 to 40°. Under the conditions where other preparation parameters are the same, the angle will affect the deposition rate of the film. Too small or too large an angle will affect the thickness of the film. When the angle is 20 to 40°, the projected area of ​​the target material relative to the substrate is relatively large, the deposition rate is relatively fast, and the efficiency is high.

[0032] Furthermore, in step 6), the total gas flow rate of argon and nitrogen remains unchanged at 40 sccm, wherein the gas flow rate of nitrogen is 4-16 sccm, wherein nitrogen accounts for 10%-40% of the total gas flow rate; correspondingly, the gas flow rate of argon is 24-36 sccm, and the purity of the two gases is ≥99.999%.

[0033] Furthermore, when the sputtering power described in step 6) is lower than the required sputtering power, the target material is not easy to ignite, while when it is higher than the required sputtering power, it is easy to cause the equipment to overheat and affect the sputtering effect.

[0034] The beneficial effects of the present invention are:

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1. A method for preparing a high-hardness Ta-Hf-W nitride film according to the present invention, wherein the prepared Ta a Hf b W c N d The reactive multi-target DC magnetron sputtering technology used in the nitride film is a method of simultaneously performing co-sputtering of multiple targets and gas reactive sputtering. The target material is a pure metal bulk target material, and the gas is high-purity argon and nitrogen. This method can avoid the complicated target material preparation process. By changing the gas flow rate of nitrogen or the sputtering time of the target material, nitride films of various chemical compositions can be prepared. This method has the characteristics of high deposition rate, wide material applicability, good repeatability, etc. Pure metal targets are used in the preparation process of the present invention, and the raw materials are simple and easy to obtain, which is suitable for large-scale industrial production.

[0037] 2. The high-hardness Ta-Hf-W nitride film of the present invention is prepared from Ta a Hf b W c N dNitride film, whose component elements are evenly distributed, has a single-phase face-centered cubic crystal structure; Ta a Hf b W c N d Nitride films not only have higher hardness and elastic modulus, but also have lower surface roughness.

[0038] 3. The high-hardness Ta-Hf-W nitride film described in the present invention contains four elements: Ta, Hf, W, and N, and can form a high-hardness nitride film with a wide range of components. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0040] Figure 1 is Ta in Example 1 of the present invention 21 Hf 17 W 31 N 31 Surface and cross-sectional morphology SEM images of nitride films;

[0041] Figure 2 is Ta in Example 1 of the present invention 21 Hf 17 W 31 N 31 Surface scanning EDS map of elements of nitride film;

[0042] Figure 3 is Ta in Example 1 of the present invention 21 Hf 17 W 31 N 31 AFM image of the surface morphology of nitride films;

[0043] Figure 4 is Ta in Example 1 of the present invention 21 Hf 17 W 31 N 31 XRD pattern of nitride film;

[0044] Figure 5 is Ta in Example 2 of the present invention 20 HkDJ 30 N 42 Surface and cross-sectional morphology SEM images of nitride films;

[0045] Figure 6 is Ta in Example 2 of the present invention 20 HkDJ 30 N 42 Surface scanning EDS map of elements of nitride film;

[0046] Figure 7 is Ta in Example 2 of the present invention 20 HkDJ 30 N 42 AFM image of the surface morphology of nitride films;

[0047] Figure 8 is Ta in Example 2 of the present invention 20 HkDJ 30 N 42 XRD pattern of nitride film;

[0048] Fig. 9 is Ta in Example 3 of the present invention 17 HkDJ 29 N 47 Surface and cross-sectional morphology SEM images of nitride films;

[0049] Fig.10 is Ta in Example 3 of the present invention 17 HkDJ 29 N 47 Surface scanning EDS map of elements of nitride film;

[0050] Fig.11 is Ta in Example 3 of the present invention 17 HkDJ 29 N 47 AFM image of the surface morphology of nitride films;

[0051] Fig.12 is Ta in Example 3 of the present invention 17 HkDJ 29 N 47 XRD patterns of nitride films.

[0052] Fig.13 This is a macroscopic morphology of the Ta—Hf—W nitride film prepared at a nitrogen flow rate of 50% in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0053] The following embodiments are used to provide a detailed and complete description of the present invention so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention, but are not used to limit the scope of the present invention.

[0054] The raw materials used in the following examples can all be purchased commercially:

[0055] 1. The purity of the high-purity argon and nitrogen used in the present invention is ≥99.999%.

[0056] 2. The purity of Ta, Hf and W target materials used in the thin film prepared by the present invention is ≥99.95%, and the single crystal silicon wafer is a commercially available product.

[0057] 3. The high vacuum magnetron sputtering coating equipment used for preparing the thin film of the present invention is a magnetron sputtering coating equipment produced by Shenyang Scientific Instrument Co., Ltd. of the Chinese Academy of Sciences; the mechanical pump and molecular pump are both supporting equipment of the high vacuum magnetron sputtering coating equipment produced by the same company.

[0058] Embodiment 1:

[0059] A method for preparing a high-hardness Ta-Hf-W nitride film, specifically Ta 21 Hf 17 W 31 N 31 A method for preparing a nitride film comprises the following steps:

[0060] The commercial P-type, crystal orientation <100> The single crystal silicon wafer is treated with damping polishing, and then ultrasonically cleaned at a frequency of 60 to 80 Hz in anhydrous ethanol for 10 minutes to remove impurities and contaminants attached to the surface of the substrate. Then, the substrate is rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface; the smooth surface of the substrate is fixed on the furnace plate facing down, and the furnace plate is fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment, and the rotating sample stage baffle is adjusted to a position that completely covers the substrate; the metal targets Ta, Hf and W are placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage are adjusted to 30°, and the vertical distance between the metal target and the sample stage is adjusted to 10 cm; the deposition chamber is first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber is evacuated to less than 6.0×10 -4Pa; high-purity argon gas with a purity of ≥99.999% at a gas flow rate of 36sccm and high-purity nitrogen gas with a purity of ≥99.999% at a gas flow rate of 4sccm were introduced into the deposition chamber, the working gas pressure was set to 0.7Pa, the sputtering power of the Ta target was set to 100W, the sputtering power of the Hf target was set to 100W, and the sputtering power of the W target was set to 100W, and the target was pre-sputtered for 10 minutes to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering was completed, the sample stage rotation rate was set to 15r / min, the sample stage baffle was opened, and formal sputtering for 1h was started; after the sputtering was completed, the DC constant current power supply was turned off, the argon switch was turned off, the sample stage rotation was stopped, and the film was cooled to room temperature in a vacuum state and then taken out to reduce oxidation contamination, and finally the Ta film was obtained on the silicon wafer. 21 Hf 17 W 31 N 31 Nitride thin films.

[0061] The chemical composition of the nitride film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the nitride film are shown in the attached drawings. Figure 1 and 2 As shown: According to the quantitative calculation results of the software, the composition of the nitride film is Ta 21 Hf 17 W 31 N 31 .

[0062] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 21 Hf 17 W 31 N 31 The surface morphology of the nitride film was analyzed using the tapping mode with a scanning area of ​​10 μm × 10 μm. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. The results are shown in the attached figure. Figure 3 Shown:Ta 21 Hf 17 W 31 N 31 The surface AFM morphology of the nitride film is a needle-like structure with a surface roughness of 2.20 nm.

[0063] The surface roughness of the film will affect the wear resistance of the film. The friction coefficient and wear rate of the film generally increase with the increase of surface roughness. This is because the rough surface has a smaller contact area and higher contact pressure, which will lead to a higher friction coefficient and wear loss. Therefore, a smaller surface roughness is conducive to improving the wear resistance of the film.

[0064] The Ta was characterized by using a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 21 Hf 17 W 31 N 31 The XRD phase analysis of the nitride film was carried out with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ = 0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in the attached figure. Figure 4 According to the lattice diffraction extinction law, it can be determined that the five diffraction peaks marked by black diamonds in the spectrum correspond to the (111), (200), (220), (311) and (222) crystal planes of the FCC structure phase, indicating that Ta 21 Hf 17 W 31 N 31 The crystal structure of the nitride film is a single-phase face-centered cubic (FCC) structure.

[0065] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 21 Hf 17 W 31 N 31 The hardness of the nitride film was tested and the results showed that Ta 21 Hf 17 W 31 N 31 The nano-indentation hardness value of the nitride film is 31.3 GPa, and the elastic modulus value is 340.5 GPa. It can be used in high-hardness and wear-resistant fields.

[0066] Embodiment 2:

[0067] A method for preparing a high-hardness Ta-Hf-W nitride film, specifically Ta 20 HkDJ 30 N 42 A method for preparing a nitride film comprises the following steps:

[0068] The commercial P-type, crystal orientation <100> The single crystal silicon wafer is treated with damping polishing, and then ultrasonically cleaned at a frequency of 60 to 80 Hz in anhydrous ethanol for 10 minutes to remove impurities and contaminants attached to the surface of the substrate. Then, the substrate is rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface; the smooth surface of the substrate is fixed on the furnace plate facing down, and the furnace plate is fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment, and the rotating sample stage baffle is adjusted to a position that completely covers the substrate; the metal targets Ta, Hf and W are placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage are adjusted to 30°, and the vertical distance between the metal target and the sample stage is adjusted to 10 cm; the deposition chamber is first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber is evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity of ≥99.999% at a gas flow rate of 32sccm and high-purity nitrogen gas with a purity of ≥99.999% at a gas flow rate of 8sccm were introduced into the deposition chamber, the working gas pressure was set to 0.7Pa, the sputtering power of the Ta target was set to 100W, the sputtering power of the Hf target was set to 100W, and the sputtering power of the W target was set to 100W, and the target was pre-sputtered for 10 minutes to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering was completed, the sample stage rotation rate was set to 15r / min, the sample stage baffle was opened, and formal sputtering for 1h was started; after the sputtering was completed, the DC constant current power supply was turned off, the argon switch was turned off, the sample stage rotation was stopped, and the film was cooled to room temperature in a vacuum state and then taken out to reduce oxidation contamination, and finally the Ta film was obtained on the silicon wafer. 20 HkDJ 30 N 42 Nitride thin films.

[0069] The chemical composition of the nitride film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the nitride film are shown in the attached drawings. Figure 5 and 6 As shown: According to the quantitative calculation results of the software, the composition of the alloy film is Ta 20 HkDJ 30 N 42 .

[0070] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 20 HkDJ 30 N 42The surface morphology of the nitride film was analyzed using the tapping mode with a scanning area of ​​10 μm × 10 μm. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. The results are shown in the attached figure. Figure 7 Shown:Ta 20 HkDJ 30 N 42 The surface AFM morphology of the nitride film is a needle-like structure with a surface roughness of 1.85 nm.

[0071] The Ta was characterized by using a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 20 HkDJ 30 N 42 The XRD phase analysis of the nitride film was carried out with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ = 0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in the attached figure. Figure 8 According to the lattice diffraction extinction law, it can be determined that the five diffraction peaks marked by black diamonds in the spectrum correspond to the (111), (200), (220), (311) and (222) crystal planes of the FCC structure phase, indicating that Ta 20 HkDJ 30 N 42 The crystal structure of the nitride film is a single-phase face-centered cubic (FCC) structure.

[0072] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 20 HkDJ 30 N 42 The hardness of the nitride film was tested and the results showed that Ta 20 HkDJ 30 N 42 The nanoindentation hardness value of the nitride film is 36.1 GPa, and the elastic modulus value is 357.2 GPa.

[0073] Embodiment 3:

[0074] A method for preparing a high-hardness Ta-Hf-W nitride film, specifically Ta 17 HkDJ 29 N 47 A method for preparing a nitride film comprises the following steps:

[0075] The commercial P-type, crystal orientation <100> The single crystal silicon wafer is treated with damping polishing, and then ultrasonically cleaned at a frequency of 60 to 80 Hz in anhydrous ethanol for 10 minutes to remove impurities and contaminants attached to the surface of the substrate. Then, the substrate is rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface; the smooth surface of the substrate is fixed on the furnace plate facing down, and the furnace plate is fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment, and the rotating sample stage baffle is adjusted to a position that completely covers the substrate; the metal targets Ta, Hf and W are placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage are adjusted to 30°, and the vertical distance between the metal target and the sample stage is adjusted to 10 cm; the deposition chamber is first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber is evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity of ≥99.999% at a gas flow rate of 24sccm and high-purity nitrogen gas with a purity of ≥99.999% at a gas flow rate of 16sccm are introduced into the deposition chamber, the working gas pressure is set to 0.7Pa, the sputtering power of the Ta target is set to 100W, the sputtering power of the Hf target is set to 100W, and the sputtering power of the W target is set to 100W, and the target is pre-sputtered for 10min to remove impurities such as oxides attached to the surface of the target; after the pre-sputtering is completed, the sample stage rotation rate is set to 15r / min, the sample stage baffle is opened, and formal sputtering for 1h is started; after the sputtering is completed, the DC constant current power supply is turned off, the argon switch is turned off, the sample stage rotation is stopped, and the film is cooled to room temperature in a vacuum state and then taken out to reduce oxidation contamination, and finally the Ta film is obtained on the silicon wafer. 17 HkDJ 29 N 47 Nitride thin films.

[0076] The chemical composition of the nitride film was analyzed using an Oxford X-act energy dispersive spectrometer (EDS, installed on a scanning electron microscope). The surface and cross-sectional morphology SEM images and element surface scanning EDS spectra of the nitride film are shown in the attached drawings. Fig. 9 and 10 As shown: According to the quantitative calculation results of the software, the composition of the nitride film is Ta 17 HkDJ 29 N 47 .

[0077] The Ta was photographed using the Dimension ICON atomic force microscope (AFM) from Bruker GmbH, Germany. 17 HkDJ 29 N 47The surface morphology of the nitride film was analyzed using the tapping mode with a scanning area of ​​10 μm × 10 μm. The surface roughness (Ra) of the film was analyzed using NanoScope Analysis software. The results are shown in the attached figure. Fig.11 Shown:Ta 17 HkDJ 29 N 47 The surface AFM morphology of the nitride film is a needle-like structure with a surface roughness of 2.06 nm.

[0078] The Ta was characterized by using a D8 Advance X-ray diffractometer (XRD) from BRUKER AXS GmbH, Germany. 17 HkDJ 29 N 47 The XRD phase analysis of the nitride film was carried out with an operating voltage of 40 kV, an operating current of 40 mA, an X-ray source of Cu-Ka (λ = 0.15418 nm) rays, a grazing incidence angle of 1°, a scanning speed of 4° / min, a scanning step of 0.02° / step, and a scanning range of 10° to 90°. The results are shown in the attached figure. Fig.12 According to the lattice diffraction extinction law, it can be determined that the five diffraction peaks marked by black diamonds in the spectrum correspond to the (111), (200), (220), (311) and (222) crystal planes of the FCC structure phase, indicating that Ta 17 HkDJ 29 N 47 The crystal structure of the nitride film is a single-phase face-centered cubic (FCC) structure.

[0079] Since the film is a micro-nanoscale material, its hardness can only be measured using a nanoindenter. Vickers hardness and Rockwell hardness are usually used to measure the hardness of alloy blocks, but cannot be used to measure the hardness of films. Therefore, the Nano Indenter G200 nanoindenter produced by Agilent Technologies was used in the continuous stiffness mode to measure the hardness of Ta. 17 HkDJ 29 N 47 The hardness of the nitride film was tested and the results showed that Ta 17 HkDJ 29 N 47 The nano-indentation hardness value of the nitride film is 28.4 GPa, and the elastic modulus value is 308.3 GPa. It can be used in high-hardness and wear-resistant fields.

[0080] Comparative Example:

[0081] The method for preparing a Ta-Hf-W nitride film comprises the following steps: preparing a Ta-Hf-W nitride film at a nitrogen flow rate of 50%:

[0082] The commercial P-type, crystal orientation <100> The single crystal silicon wafer is treated with damping polishing, and then ultrasonically cleaned at a frequency of 60 to 80 Hz in anhydrous ethanol for 10 minutes to remove impurities and contaminants attached to the surface of the substrate. Then, the substrate is rinsed with deionized water and then blown dry with compressed nitrogen to prevent residual water stains on the surface; the smooth surface of the substrate is fixed on the furnace plate facing down, and the furnace plate is fixed on the sample stage of the deposition chamber of the magnetron sputtering thin film deposition system equipment, and the rotating sample stage baffle is adjusted to a position that completely covers the substrate; the metal targets Ta, Hf and W are placed on three different DC target positions in the deposition chamber respectively, and the angles of each metal target perpendicular to the center line of the sample stage are adjusted to 30°, and the vertical distance between the metal target and the sample stage is adjusted to 10 cm; the deposition chamber is first evacuated to less than 8.0 Pa by a mechanical pump, and then the vacuum degree of the deposition chamber is evacuated to less than 6.0×10 -4 Pa; high-purity argon gas with a purity greater than or equal to ≥99.999% and high-purity nitrogen gas with a purity greater than or equal to ≥99.999% at a gas flow rate of 20sccm and a gas flow rate of 20sccm are introduced into the deposition chamber, the working gas pressure is set to 0.7Pa, the sputtering power of the Ta target is set to 100W, the sputtering power of the Hf target is set to 100W, and the sputtering power of the W target is set to 100W, and the target material is pre-sputtered for 10 minutes to remove impurities such as oxides attached to the surface of the target material; after the pre-sputtering is completed, the sample stage rotation rate is set to 15r / min, the sample stage baffle is opened, and formal sputtering for 1h is started; after the sputtering is completed, the DC constant current power supply is turned off, the argon switch is turned off, the sample stage rotation is stopped, the film is cooled to room temperature in a vacuum state and then taken out to reduce oxidation contamination, and finally a Ta-Hf-W nitride film prepared at a nitrogen flow rate of 50% is obtained on a silicon wafer.

[0083] Fig.13 The macroscopic morphology of the Ta-Hf-W nitride film prepared at a nitrogen flow rate of 50%.

[0084] It shows that when the nitrogen flow rate is 50%, cracks occur on the surface of the Nb-Ta-WN film. The nitrogen content of the Nb-Ta-WN film increases sharply with the increase of the nitrogen flow rate, and the nitrogen content rises to 47% and reaches saturation when the nitrogen flow rate is 40%. This shows that the nitride film prepared under the process condition of 50% nitrogen flow rate should have the maximum residual stress, which leads to cracking of the film.

[0085] The properties of the Ta—Hf—W nitride films obtained in the examples and comparative examples are shown in Table 1 below.

[0086] Table 1

[0087] Surface roughness hardness Elastic modulus Example 1 2.20nm 31.3GPa 340.5GPa Example 2 1.85nm 36.1GPa 357.2Gpa Example 3 2.06nm 28.4GPa 308.3Gpa Comparative Example / / /

[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high hardness Ta-Hf-W nitride film, characterized in that: It's her a Hf b W c N d The nitride film is composed of Ta, Hf, W, and N atoms, and the chemical formula is: Ta a Hf b W c N d ; wherein a, b, c and d all represent atomic ratios, the value range of a is: 17-21; the value range of b is: 7-17; the value range of c is: 29-31; the value range of d is: 31-47, and a+b+c+d=100; Ta, Hf, and W targets are prepared by reactive magnetron sputtering thin film deposition at set sputtering powers and different nitrogen gas flow rates to obtain Ta a Hf b W c N d Nitride film; the nitride film has four components, a single-phase face-centered cubic crystal structure, a surface roughness of 1.85-2.20 nm, a hardness of 28.4-36.1 GPa, and an elastic modulus of 308.3-357.2 GPa.

2. The method for preparing a high-hardness Ta-Hf-W nitride film according to claim 1, characterized in that: The following steps are involved: 1) Place the substrate in anhydrous ethanol and perform ultrasonic cleaning for 10 minutes to remove pollutants attached to the surface of the substrate, and then rinse the substrate with deionized water; 2) Blow dry the cleaned substrate with compressed nitrogen to make the surface of the substrate clean and prevent water stains from remaining; 3) Fix the substrate with its smooth surface facing downward on a furnace plate, fix the furnace plate on a sample stage in a deposition chamber of a magnetron sputtering thin film deposition device, and rotate the sample stage baffle to adjust it to a position that completely covers the substrate; 4) placing Ta, Hf and W metal bulk targets respectively on three different DC target positions in the deposition chamber, and adjusting the angle of each target perpendicular to the center line of the sample stage and the vertical distance between each target and the sample stage; The targets of Ta, Hf and W are all high-purity metal blocks with a purity of ≥99.95%, a diameter of 60 mm and a thickness of 3 to 5 mm; The angle of the target relative to the center line of the sample stage is 20 to 40 degrees; the vertical distance between the metal target of Ta, Hf, W and the sample stage is 5 to 15 cm; 5) First, use a mechanical pump to evacuate the deposition chamber to a vacuum level of less than 8.0 Pa, and then use a molecular pump to evacuate the deposition chamber to a vacuum level of less than 6.0×10 -4 ~8.0×10 -4 Pa; 6) Then, argon and nitrogen are introduced into the deposition chamber, and the gas flow rates are adjusted respectively, and the working pressure is adjusted to 0.7-0.9 Pa, and the DC power supply of the corresponding target is turned on, and the sputtering power of the target is set respectively, and the target is pre-sputtered for 10-15 minutes to remove oxide impurities formed on the surface of the target, wherein the sputtering power of the Ta target is 100 W, the sputtering power of the Hf target is 100 W, and the sputtering power of the W target is 100 W; 7) Setting the rotation rate of the sample stage to 15-30 r / min, opening the substrate baffle, and performing sputtering deposition on the smooth surface of the substrate for 1 h to obtain a thin film; 8) After the sputtering deposition is completed, turn off the DC power supply, turn off the argon and nitrogen, stop the rotation of the sample stage, and let the film cool to room temperature under vacuum before taking it out to reduce oxidation contamination. Finally, Ta is obtained on the substrate. a Hf b W c N d The nitride film is a high-hardness Ta-Hf-W nitride film. The nitride film is composed of Ta, Hf, W, and N atoms, and the chemical formula is: Ta a Hf b W c N d ; Wherein, a, b, c and d all represent atomic ratios, the value range of a is: 17~21; the value range of b is: 7~17; the value range of c is: 29~31; the value range of d is: 31~47, and a+b+c+d=100; the number of components of the nitride film is quaternary, with a single-phase face-centered cubic crystal structure, a surface roughness of 1.85~2.20nm, a hardness of the film is 28.4~36.1GPa, and an elastic modulus is 308.3~357.2GPa.

3. The method for preparing a high hardness Ta-Hf-W nitride film according to claim 2, characterized in that: Before the ultrasonic cleaning in step 1), the smooth surface of the substrate is polished with a damping cloth.

4. The method for preparing a high hardness Ta-Hf-W nitride film according to claim 2, characterized in that: The ultrasonic cleaning in step 1) has an ultrasonic frequency of 60 to 80 Hz.

5. The method for preparing a high hardness Ta-Hf-W nitride film according to claim 2, characterized in that: The substrate in step 1) is a single crystal silicon wafer, which is a commercial P-type silicon wafer with a crystal orientation of <100> .

6. The method for preparing a high hardness Ta-Hf-W nitride film according to claim 2, characterized in that: In step 6), the total gas flow rate of argon and nitrogen remains unchanged at 40 sccm, wherein the gas flow rate of nitrogen is 4-16 sccm, of which nitrogen accounts for 10%-40% of the total gas flow rate; correspondingly, the gas flow rate of argon is 24-36 sccm, and the purity of the two gases is ≥99.999%.

Citation Information

Patent Citations

  • Nb-Ta-W multi-principal element alloy film and preparation method thereof

    CN114015995A

  • Tungsten-doped tantalum-hafnium carbide thin film material and preparation method thereof

    CN114959572A

  • Ultrahigh-temperature high-strength tantalum alloy and preparation method thereof

    CN116676519A

  • High-hardness Nb-Ta-W nitride film and preparation method thereof

    CN117089808A